Motivations of wheelchair curling athletes to participate in sport: a qualitative research - Daskesen, S. S.; Bedir, D.; Ilhan, E. L.; Demir Onur, T.; Mair, H. (Frontiers in Psychology, 2025)
Introduction: Self-Determination Theory (SDT) is a holistic approach that provides a comprehensive framework for understanding individuals` intrinsic and extrinsic motivations, analyzing the nature of motivation and its relationship with psychological development. This study employs the SDT framework to examine the motivational processes of wheelchair curling athletes.